Operations strategy: a decision and evaluation framework - Van Mieghem, Jan A. (Henry Stewart Talks, 2012)
Operations management, Concept, Framework, Resource view, Process view, Competency view, Operating system of the firm, A strategic framework for operations, Principle of alignment, Principle of value maximization, VCAP framework, Operational focus, Tradeoff curves, Efficient frontier, Separating complexity and simplicity, Operational competency space
Reviewed at 2016/10/31